Cognitive and behavioral phenotype of children with pseudohypoparathyroidism type 1A. Issue 2 (28th November 2017) - Perez, Katia M.; Lee, Evon B.; Kahanda, Sachini; Duis, Jessica; Reyes, Monica; Jüppner, Harald; Shoemaker, Ashley H.
Abstract : Pseudohypoparathyroidism 1A (PHP1A) is a rare, genetic disorder. Most patients with PHP1A have cognitive impairment but this has not been systematically studied. We hypothesized that children with PHP1A would have lower intelligent quotient (IQ) scores than controls. To evaluate cognition and behavior, we prospectively enrolled children with PHP1A, one unaffected sibling (when available) and controls matched on BMI/age/gender/race. Evaluations included cognitive and executive function testing. Parents completed questionnaires on behavior and executive function. We enrolled 16 patients with PHP1A, 8 unaffected siblings, and 15 controls. Results are presented as mean (SD). The PHP1A group had a composite IQ of 85.9 (17.2); 25% had a composite IQ < −2 SD. The PHP1A group had significantly lower IQs than matched controls (composite IQ −17.3, 95%CI −28.1 to −6.5, p  < 0.01) and unaffected siblings (composite IQ −21.5, 95%CI −33.9 to −9.1, p  < 0.01). Special education services were utilized for 93% of the patients with PHP1A. Deficits were observed in executive function and parents reported delayed adaptive behavior skills and increased rates of attention deficit hyperactivity disorder. In conclusion, children with PHP1A have lower intelligence quotient scores, poorer executive function, delayed adaptive behavior skills, and increased behavior problems.